CHILDREN'S INHERITANCE RIGHTS TO MIXED MARRIAGE WHAT IS NOT RECORDED IN PERSPECTIVE INTERNATIONAL CIVIL LAW - Fitra Deni; Upik Mutiara (Universitas Muhammadiyah Tangerang, 2021)
This article aims to find out the protection of the inheritance rights of children of mixed marriages that are not recorded in the perspective of the Indonesian International Civil Law (HPI Indonesia). The research in this article is doctrinal legal research or dogmatic, or normative juridical method or also referred to as literature law research, with the method of deduction reasoning. This method of deduction reasoning is used to conclude things that are general to a special thing which is then drawn into a conclusion. The results of this article show that the law applicable to mixed marriages can be seen based on the principles of HPI Indonesia including the principle of lex loci celebrationis, joint nationality or joint residence, where the marriage takes place, where the husband and wife become citizens after marriage or the residence of the husband and wife. But for mixed marriages that are not recorded according to the applicable rules do not eliminate the inheritance of the child, especially from the father as long as there is recognition with an authentic deed. Not noting the marriage does not mean the marriage becomes void but only has not been recognized that there has been a mixed marriage so that the rights of the child are not obtained as they should be. It's just that children born from marriage are considered children outside of marriage. Constitutional Court Decision No. 46/PUU-VIII/2010 is a new legal breakthrough in which children born outside of marriage from unrecorded mixed marriages still have a civil relationship with both parents. So that with the unrecorded of mixed marriage does not eliminate the civil rights of children as legal heirs.